IDENTIFIKASI DAN ANALISIS GINI RATIO KABUPATEN GORONTALO - Harijono Imbran (Universitas Muhammadiyah Gorontalo, 2018)
This study aims to analyze and identify the level of income inequality using the Gini Ratio approach. The data sources used in this study are primary and secondary data obtained through observation and data collection reports both from Gorontalo District Statistic Center (BPS) and Gorontalo District Regional Development Planning Agency (BAPPEDA), such as Districts in Figures and Indicators of Welfare Results National Census. Data sourced from Bappeda and BPS in the form of per capita Gross Regional Domestic Product data on the basis of Constant Prices, and data on consumption per capita average. The results of the study show that the Gorontalo Regency Gini Ratio in the period 2012 - 2017 is in the moderate range (> 0.4) or at moderate or moderate levels.Keywords: Identification, Analysis, Gini Ratio